IMPLEMENTATION OF THE PROGRAM FOR HANDLING CASES OF VIOLENCE AGAINST CHILDREN IN LHOKSEUMAWE CITY - Ti Aisyah (Bajang Institute, 2025)
Comfort and safety in the driver's seat of a military vehicle are crucial aspects Cases of violence against children have increased and ebbed and flowed in Lhokseumawe City. From 2019-2020, the increase in cases of violence against children was above 20 cases per year. This study aims to analyze and describe how the implementation of the program for handling cases of violence against children and analyze what are the obstacles that occur in handling cases of violence against children in Lhokseumawe City. This research uses a qualitative approach with a descriptive method. Data collection techniques with observation, interviews, and documentation. The results of this study show that the program for handling cases of violence against children has not been running well. The communication aspect of the program has not been optimally implemented, while the disposition of the attitude of the implementors has not been persuasive action, The service of handling cases of violence is still unsatisfactory because there are still public complaints about the handling of cases, which is due to the high number of cases of violence against children in 2022 reaching 27 cases. With this problem, the City Government of Lhokseumawe must continue to improve its performance optimally and thoroughly both in forming policies and implementing programs optimally and thoroughly to all relevant institutions and elements of society, so that acts of violence against children do not occur again. In addition, the obstacles to the implementation of the program are the lack of a budget, the law that has not been firm, the public perception of handling cases is still negative, and it does not support the program